Involvement of the peripheral nervous system in human prion diseases including dural graft associated Creutzfeldt–Jakob disease. Issue 3 (16th February 2005) - Ishida, C; Okino, S; Kitamoto, T; Yamada, M
Abstract : Objective: To investigate abnormal prion protein (PrP) deposition in the peripheral nervous system (PNS) in human prion diseases. Methods: Eight patients with prion diseases were examined: three with sporadic Creutzfeldt–Jakob disease (sCJD), two with dural graft associated CJD (dCJD), one with Gerstmann–Sträussler–Scheinker disease (GSS) with a PrP P102L mutation (GSS102), and two with a P105L mutation (GSS105). An atypical case of sCJD with PrP plaques in the brain presented clinically with peripheral neuropathy, and showed demyelination in 12% of the teased fibres of the sural nerve. The PNS was investigated by immunohistochemical and western blotting analyses of PrP. Results: In immunohistochemical studies, granular PrP deposits were detected in some neurones of dorsal root ganglia and a few fibres of peripheral nerves and spinal posterior roots in one sCJD and two dCJD patients, but not in GSS102 or GSS105 patients. The atypical case of sCJD with peripheral neuropathy showed no obvious PrP deposition in the nerves. Western blotting analysis of the PNS from the dCJD patients revealed a small amount of protease K resistant PrP in the dorsal root ganglia and peripheral nerves. Conclusions: Abnormal PrP deposition occurs in the dorsal root ganglia and peripheral nerves in sCJD and dCJD. The PrP deposits in the PNS are not correlated with clinical manifestation of peripheral neuropathy in CJD.